PENGARUH STRUKTUR MODAL, LIKUIDITAS DAN JUMLAH PINJAMAN YANG DISALURKAN TERHADAP PROFITABILITAS PADA PT BANK PANIN DUBAI SYARIAH Tbk PERIODE 2011-2018 - galuh septiana (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2023)
This study aims to determine the effect of capital structure, liquidity (cash ratio) on profitability (return on assets) both partially and simultaneously on PT Bank Panin Dubai Syariah Tbk which is listed on the IDX for the period 2011-2018. The data used is secondary data. Data collection uses documentation and literature study techniques. The sampling technique uses purposive sampling method.Data analysis techniques used include the classic assumption test, multiple linear regression analysis and hypothesis testing consisting of t test and F test. The t test aims to determine the effect partially and the F test aims to determine the effect simultaneously. The results showed that: (1) Capital structure has a positive but not significant effect on profitability with a sig value of 0.433 (0.433> 0.05). (2) liquidity has a positive and significant effect on profitability with a sig value of 0.037 (0.037 <0.05). (3) Loans have a positive but not significant effect on profitability with a sig value of 0.670 (0.670> 0.05). (4) Capital structure, liquidity and the number of loans channeled together or simultaneously have a positive but not significant effect on profitability with a sig value of 0.173 (0.173> 0.05). Keywords: Capital structure, Liquidity, Loans and Profitability